Pengaruh Penggunaan Informasi Akuntansi, Pelatihan Akuntansi Dan Modal Terhadap Keberhasilan Usaha Kecil Dan Menengah (Studi Empiris Di Kota Lhokseumawe) - fatmawati fatmawati; Muhammad Yusra; Muammar Khadaffi; Mardiaton Mardiaton (Jurnal Akuntansi Malikussaleh (JAM), 2023)
This research aims to determine the use of accounting information, accounting training and capital on the success of small and medium enterprises in Lhokseumawe City. The population in this research is all SMEs in Lhokseumawe City, numbering 6,353 UKM. The sampling technique used was the random sampling method with a sample size of 99 respondents. The type of data used is quantitative data. The data sources in this research are primary data, which was obtained in the form of interviews with several UKM owners and surveys (questionnaires) with UKM owners, and secondary data used in this research includes library materials, literature, previous research, and so on. Data analysis in this research used the SPSS program.